G6PD deficiency triggers dopamine loss and the initiation of Parkinson’s disease pathogenesis - Morgan G. Stykel; Shehani V. Siripala; Eric Soubeyrand; Carla L. Coackley; Ping Lu; Suelen Camargo; Sharanya Thevasenan; Gerardo Balderas Figueroa; Raphaella W.L. So; Erica Stuart; Rachi Panchal; Elissavet-Kalliopi Akrioti; et al. (Cell Reports)
Summary: Loss of dopaminergic neurons in Parkinson’s disease (PD) is preceded by loss of synaptic dopamine (DA) and accumulation of proteinaceous aggregates. Linking these deficits is critical to restoring DA signaling in PD. Using murine and human pluripotent stem cell (hPSC) models of PD coupled with human postmortem tissue, we show that accumulation of α-syn micro-aggregates impairs metabolic flux through the pentose phosphate pathway (PPP). This leads to decreased nicotinamide adenine dinucleotide phosphate (NADP/H) and glutathione (GSH) levels, resulting in DA oxidation and decreased total DA levels. We find that α-syn anchors the PPP enzyme G6PD to synaptic vesicles via the α-syn C terminus and that this interaction is lost in PD. Furthermore, G6PD clinical mutations are associated with PD diagnosis, and G6PD deletion phenocopies PD pathology. Finally, we show that restoring NADPH or GSH levels through genetic and pharmacological intervention blocks DA oxidation and rescues steady-state DA levels, identifying G6PD as a pharmacological target against PD.